Methodology for Calculating Course Errors when Aiming an Aircraft at a Maneuvering Air Target - D. V. Vysotski; E. I. Khizhniak; A. V. Khizhniak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The article presents theoretical calculations that explain the origin of errors in the course of an aircraft in an automated control system when pointing at a maneuvering air target. The peculiarity of pointing at a maneuvering target is related to the execution of turns, which are characterized by overloads. The curvature of the trajectory in such areas is usually approximated by a circle of a certain radius, depending on the value of the overload and flight speed to intercept. In the automated control system, the current course of the aircraft is determined as the direction of movement by two marks corresponding to the current and previous moments of information update time. For a target moving in a straight line, this approach is valid. However, in a turn where the guidance path is a curved line, the true heading will correspond to the tangent at the turn point. The difference in these approaches determines the error of the course calculation. This article provides a formulaic calculation of turn radii for flight speeds to intercept an air target and overloads, as well as the calculation of true and current courses. The peculiarity of the methodology is a strict formalized mathematical description. The article presents the dependences of heading errors from the aircraft’s intercept flight speed and overloads using the example of the Su-27 multifunctional fighter.